PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS CANVA PADA MATERI KONSEP MANAJEMEN TERHADAP PEMAHAMAN MAHASISWA - Munthe, Raja Parnaungan; Revita Yuni; Wendi Rehan Situmorang; Icha Lesmana; Siti Sarah Tumangger (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to investigate the impact of implementing a Canva-based learning tool on students' understanding of Management Concepts. The research stemmed from the problem of low student understanding, caused by traditional teaching methods that lack diversity and underutilize visual elements. This study employed a quantitative method through an explanatory research approach. The sample size reached 50 students, selected using a purposive sampling technique. The data collection tool was a Likert-scale questionnaire, which was verified for its validity and reliability. Data analysis involved checking for validity, reliability, normality, linearity, and simple linear regression. The main findings showed that the use of Canva had a positive and significant impact on student understanding. The coefficient of determination (R²) of 0.668 indicated that Canva contributed approximately 66.8% to the increase in understanding, with the remainder influenced by other factors. These results reinforce the idea that Canva can help students digest abstract management concepts through more engaging, organized, and easily digestible visualizations. Ultimately, this study recommends that Canva be used as an alternative teaching medium in courses requiring conceptual understanding.